2010
DOI: 10.21136/mb.2010.140704
|View full text |Cite
|
Sign up to set email alerts
|

Li-Yorke pairs of full Hausdorff dimension for some chaotic dynamical systems

Abstract: pairs of full Hausdorff dimension for some chaotic dynamical systems

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 11 publications
(13 reference statements)
0
11
0
Order By: Relevance
“…In the same setting, F. Blanchard et al in [4] shown that if the topological entropy of (X, f ) is positive, then (X, f ) is Li-Yorke chaotic. The dimensional properties of the sets given in Definition 1.1 have received attention recently -see [22]. 1.2.…”
Section: Introduction and Statement Of Resultsmentioning
confidence: 99%
“…In the same setting, F. Blanchard et al in [4] shown that if the topological entropy of (X, f ) is positive, then (X, f ) is Li-Yorke chaotic. The dimensional properties of the sets given in Definition 1.1 have received attention recently -see [22]. 1.2.…”
Section: Introduction and Statement Of Resultsmentioning
confidence: 99%
“…The sizes of the scrambled sets have been considered for many dynamical systems from the sense of the measure, dimension, and topology, see also [2], [16], [17], [22], [23] etc. In 1995, Xiong [25] proved that there exists a scrambled set of {1, 2, • • • , N } N of full Hausdorff dimension .…”
Section: Introductionmentioning
confidence: 99%
“…Li-Yorke pairs are the pairs of points that approach each other for some sequence of moments in the time evolution and that remain separated for other sequences of moments. In [5] was discussed on the Hausdorff dimension of the set of Li-Yorke pairs for some simple classical chaotic dynamical systems. It showed that, if the dynamical system in its invariant set is topologically conjugate to the full shift symbolic dynamical system and its invariant set is self-similar or a product of self-similar sets, then its Li-Yorke pairs have full Hausdorff dimension in the invariant set.…”
Section: Introductionmentioning
confidence: 99%
“…It showed that, if the dynamical system in its invariant set is topologically conjugate to the full shift symbolic dynamical system and its invariant set is self-similar or a product of self-similar sets, then its Li-Yorke pairs have full Hausdorff dimension in the invariant set. This result can be applied to simple classical models of "chaotic" dynamics like the tent map, the Bakers transformation, Smales horseshoe, and solenoid-like systems (see [5]) since these kinds of systems have invariant sets of self-similar or a product of self-similar sets in which the systems are topologically conjugate to full shift. To prove that Li-Yorke pairs have full dimension for more general hyperbolic systems could be a task for further research [5], which is one topic we are going to study in this paper.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation